A cognitive behavioral program to acquire social skills for students with learning difficulties - Adel Al-Sharhan, Fawaz (International Journal of Psychosocial Rehabilitation, 2024)
Difficulties is one of the fields that researchers have paid attention to ،because they know that the rate of learning difficulties among children reaches 43% among children in the field of special education, ،and learning difficulties result in behavioral effects, ، deficiencies in social skills, and the occurrence of cognitive and behavioral disturbances. Most researchers in this field believe that the need for social skills training is considered a fundamental part and component of the transitional program for all stages and life periods that a child with learning difficulties experiences. Therefore, ،this study came with the aim of developing and proposing a cognitive behavioral program to gain social skills for students with learning difficulties. About the study sample ،it is consisted of 26 male students and 29 female students in the third grade of primary in AlFahaheel Model School in Kuwait. The researcher followed the descriptive and analytical approach in order to describe the phenomena in theory as they exist in reality ،and then analyze their characteristics that distinguish them and determine the factors that cause them, ،but the quantitative approach is used to convert the qualitative data into quantitative. As for the study tools, ،the researcher has used picture and electronic books and published references dealing with the same topic in order to write the theoretical framework. And Walker-McConnell Scale of Social Competence and School Adjustment tool to analyze the answers statistically and graphically. That study indicated in its results that: a. The training program simulates an organized experience for a number of individuals who were found to have a direct need for obtaining that training. B. The training experience is considered a relatively new experience because it is considered unfamiliar with the academic education that children receive throughout the study period, which indicates the novelty of this program in the framework of the topics it deals with and how it is presented as well. C. This program creates an opportunity for students to participate and delve into the issue of acquiring and identifying various skills. Dr.. The activities and tasks of the program, in addition to the roles and positions that were practiced within its framework, were characterized by high rates of attractiveness and compatibility with the characteristics of individuals from the study sample. E. The program provided support for the family's role in developing their children's skills in social terms by introducing parents, in a written style, to the objectives of the training program as well as the skills that the program intends to impart to students.